Compton Camera Imaging of a Gamma‐Ray Glow From a Thunderstorm. Issue 19 (29th September 2022) - Kuriyama, E.; Masubuchi, M.; Koshikawa, N.; Iwashita, R.; Omata, A.; Kanda, T.; Kataoka, J.; Tsurumi, M.; Diniz, G.; Enoto, T.; Wada, Y.
Abstract: Gamma‐ray glows associated with thunderclouds have been observed since the 1980s, however it remains unclear how, and at which thunderstorms gamma‐ray glows are generated in dense atmospheres. In this study, we report the first Compton camera imaging of a gamma‐ray glow from a winter thundercloud. On 14 January 2022, using two identical Bi4 Ge3 O12  scintillators in energy range of 0.05–5 MeV, we detected two gamma‐ray glows lasting ∼4 min in a mountain area 25 km from the Japan Sea and 410 m above sea level. The same events were also observed by the Compton camera, where the first glow we observed suggested statistically significant (4.0 and 5.9 σ level) signals of two enhanced concentrations in gamma‐ray photon images in a range of 0.15–1.5 MeV. These concentrations were most clearly observed in a time window of Δ t  = 50 s around the peak intensity of the gamma‐ray glow. Plain Language Summary: Observations of gamma rays from thunderclouds started in 1980s, leading to intensive studies in the last 40 years. However, the question of where and how such gamma rays are produced in thunderclouds remains unclear, as no gamma‐ray images have been obtained to date. This paper presents the first successful gamma‐ray imaging of a thundercloud in a winter of Japan. In particular, we installed a Compton camera of 10 × 10 cm 2 in size, that is a compact but high sensitivity camera originally developed in the field of astronomy to observe gamma‐ray sky. At the peak of a gamma‐ray emission, we detected significant enhancements in the gamma‐ray photon image. The image provides the source position and beam pattern of the gamma‐ray emission, thus may be connected to highly electrified region and electron acceleration inside thunderclouds. Key Points: Gamma‐ray glows were observed in a mountainous area 25 km from the Japan Sea and 410 m above sea level on 14 January 2022, during winter One of the glows suggested two enhanced concentrations in gamma‐ray images, which was taken for the first time with a Compton camera The first successful gamma‐ray imaging provides a new means of investigating radiation beam pattern of gamma‐ray glows in thunderclouds